On fermionic shadow wave functions for strongly correlated multi-reference systems based on a single Slater determinant - Calcavecchia, Francesco; Kühne, Thomas D. (EPL - Europhysics Letters, 2015)
We demonstrate that extending the shadow wave function to fermionic systems facilitates to accurately calculate strongly correlated multi-reference systems such as the stretched H2 molecule. This development considerably extends the scope of electronic-structure calculations and enables to efficiently recover the static correlation energy using just a single Slater determinant.
CRIS-Team Scopus Importer:2023-03-20